2019
DOI: 10.12775/dem.2019.001
|View full text |Cite
|
Sign up to set email alerts
|

Revisiting the Import Demand Function: A Comparative Analysis

Abstract: This study attempts to revisit import demand function across three panels of frontier, emerging, and developed economy from 1980 to 2016. Long-run relationship exists among import demand, relative price, exchange rate, and real GDP in economy. Due to increase in real GDP, import demand responds positively across economies. It responds in same direction in short-run in frontier and emerging economies with relative price unlike that of long-run in same economies. However, it responds in same direction with relat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 34 publications
0
3
0
Order By: Relevance
“…Although the price of imports is conventionally expected to have a negative relationship with import demand, there are some cases in which evidence points to a positive relationship between the two variables. In one of the recent studies conducted in various economies, Hossain et al (2019) found a positive relationship between the relative price and import demand in the case of developing countries in both the short run and the long run. Similarly, Durmaz and Lee (2015) confirmed a positive relationship between the relative price and import demand in Turkey, implying that the trade balance might deteriorate if the import growth continues to surpass the export growth.…”
Section: Literature Reviewmentioning
confidence: 95%
See 1 more Smart Citation
“…Although the price of imports is conventionally expected to have a negative relationship with import demand, there are some cases in which evidence points to a positive relationship between the two variables. In one of the recent studies conducted in various economies, Hossain et al (2019) found a positive relationship between the relative price and import demand in the case of developing countries in both the short run and the long run. Similarly, Durmaz and Lee (2015) confirmed a positive relationship between the relative price and import demand in Turkey, implying that the trade balance might deteriorate if the import growth continues to surpass the export growth.…”
Section: Literature Reviewmentioning
confidence: 95%
“…Evidence shows that while some studies find a negative price elasticity in the import demand function (Agbola & Damoense, 2005;Arize & Afifi, 1987;Kreinin, 1973), other studies have witnessed an insignificant price elasticity (Gumede, 2000) or a positive price elasticity (Durmaz & Lee, 2015;Hossain et al, 2019;Zhou & Dube, 2011). The latter category of studies is usually based in countries whereby imports are dominated by intermediate and capital goods required for economic development.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Based on these findings, the study further recommended an increase in income and trade restriction, and a review of investment climate to stimulate growth in the Nigerian economy. Hossain et al (2019) examined the impact of gross domestic product, relative prices, and exchange rate on import demand using three panels of eight frontier countries, eight emerging countries, and ten developed countries from 1980 to 2016. The study employed panel cointegration tests and the results confirmed that import demand is determined by gross domestic product, relative prices, and exchange rate, both in the long run and the short run.…”
Section: Literature Reviewmentioning
confidence: 99%